The Question of Corruption During Releasement on Parole - A. N. Myakhanova; D. V. Sinkov (Сибирское юридическое обозрение, 2018)
The article notes that the existing corruption manifestations in the criminal-executive system, including when deciding on the conditional early release of a person serving a sentence of imprisonment, have become quite frequent. An analysis of the explanations of the Supreme Court of the Russian Federation is given, which pays special attention to the issue of parole. It is noted that his explanations are designed not only to streamline the process of parole, but also to really help to release those who are not dangerous to society. To exclude violations when applying parole, which are analyzed in the article, it is necessary to take a number of measures within the framework of reforming the penal system.